METODE CERITA DALAM PENDIDIKAN ISLAM DI TK AL MUKMINUN NGRAMBE - Luluk Musasomah (JIE (Journal of Islamic Education), 2017)
Education is a process of changing the attitude and behavior of a person or group in an effort to mature man through the effort of teaching and training, process, deed, and how to educate. The definition of education that education is the conscious guidance by educators of the physical and spiritual development of the well-educated toward the perfect human formation. It is thus commensurate with the context of Islamic education in the form of a transfer of value developed in the framework of behavior change, by steps through making the students as a more complete human being in their religious dimension. Al Mukminun kinder garden is as an educational institution, in it contains various kinds of activities and lessons both implemented in the classroom and outside the classroom, and with various methods, such as methods of playing, telling stories, singing and others. Concerning many methods used in the educational process, in this study, the author will limit the problem or focus on the method of story in Islamic education. From the explanation and affirmation of some of the terms intended, seen how the application and influence of story methods in Islamic education are implemented and developed in Al Mukminun kindergarten in order to build quality children in characteristic, healthy and have skill.